(untitled) (Proceedings of the International Conference on Future of Education, 2020)
International Degree Programmes emerged as a domestic option affiliated to private higher educational institutes (PHEIs). As it is highly competitive, PHEIs implement their BD programmes differently to attract prospective student where social media platforms use to disseminate more informed information. However, this study attempts to discuss how undergraduates seek information at an early stage of their decision-making process when selecting a BD. The questionnaire with 59 predefined variables administered by 420 first-year undergraduates from randomly selected 7 PHEIs. Educating stakeholders for the digital world is significant since the penetration of social media still plays a secondary role in seeking information.